2019
DOI: 10.29252/j.health.10.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Enclosure in Order to Control the Equipment Noise in Screw Manufacturing Industry

Abstract: Background & objectives: Noise reduction in the source is always in priority. For acoustic engineers, taking a systematic approach and considering small details of designing an enclosure can be one of the most effective ways of noise reduction. This study was carried out to detect major noise generator sources in a screw manufacturing company. Methods: In this interventional study, primarily information were collected, including machines' specifications, number of workers exposed to noise, time of exposure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The neighborhoods with the highest demand are 415, 413, 407, 406, and 405, respectively. Golmohammadi and Aliabadi [ 31 ] showed that the main external source in medical centers is traffic noise, which is unavoidable, continuous, and increasing. In this study, the sound level varies between 69.65 and 90.79 dB; which indicates that the studied hospitals suffer from noise pollution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neighborhoods with the highest demand are 415, 413, 407, 406, and 405, respectively. Golmohammadi and Aliabadi [ 31 ] showed that the main external source in medical centers is traffic noise, which is unavoidable, continuous, and increasing. In this study, the sound level varies between 69.65 and 90.79 dB; which indicates that the studied hospitals suffer from noise pollution.…”
Section: Resultsmentioning
confidence: 99%
“…Urban road traffic is the most significant external source of noise in hospitals, which is unavoidable, continuous, and increasing. Therefore, it is important to pay close attention to the demand for traffic noise reduction in the patient’s recovery process [ 31 ]. Residential areas are the other sensitive land use that can adversely affect the physiological and psychological well-being of citizens.…”
Section: Introductionmentioning
confidence: 99%